Robbing Peter to pay Paul: changing clientelist patterns in East Timor's 2017 parliamentary elections. Issue 7 (3rd October 2019) - Scambary, James
ABSTRACT: This article examines the adverse impact of clientelist relations between political parties and campaign donors on parties' relations with voters. Clientelism is generally conceptualized as a vertical, pyramid structure, whereby resources are distributed from politicians to voters at the base through brokers or programmatic politics. As Gherghina and Volintiru 1 contend, what is often overlooked is that in tandem with this vertical relationship with voters there is a complementary horizontal relationship with party donors. Parties with a weak organizational base focus on relations with party donors, such as private contractors, at the expense of their relationship with voters. Drawing on fieldwork conducted during East Timor's 2017 parliamentary elections, I engage with Gherghina and Volintiru's framework to argue that a bi-dimensional approach is integral to both understanding electoral outcomes and economic trajectories in developing country contexts. In East Timor, despite a decade of rampant patronage politics, the incumbent CNRT party's prioritization of their relationship with party donors cost them the election. In turn, this focus on party donors has distorted policy and public spending priorities, with severe implications for future development.